2013
DOI: 10.1021/jo4014113
|View full text |Cite
|
Sign up to set email alerts
|

“Bridged” n→π* Interactions Can Stabilize Peptoid Helices

Abstract: Peptoids are an increasingly important class of peptidomimetic foldamers comprised of N-alkylglycine units that have been successfully developed as antimicrobial agents, lung surfactant replacements, enzyme inhibitors, and catalysts, among many other applications. Since peptoid secondary structures can be crucial to their desired functions, significant efforts have been devoted to developing means of modularly controlling peptoid backbone amide cis-trans isomerism using side chains. Strategic engineering of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…Peptoids have been shown to adopt stable and well defined structures in solution, such as the peptoid helix, threaded loop conformation, peptoid nanosheets, and nanotubes . Unlike peptides where regular backbone hydrogen bonding helps to stabilise the secondary structures adopted, peptoids typically rely upon the local steric or electronic effects of side chains to help stabilise any secondary structures formed. The positioning of the side chains on the nitrogen of the amide (as opposed to the alpha‐carbon) also renders the backbones of peptoid sequences achiral and the tertiary amides are more easily isomerised between cis and trans conformations than the secondary amides of a peptide (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Peptoids have been shown to adopt stable and well defined structures in solution, such as the peptoid helix, threaded loop conformation, peptoid nanosheets, and nanotubes . Unlike peptides where regular backbone hydrogen bonding helps to stabilise the secondary structures adopted, peptoids typically rely upon the local steric or electronic effects of side chains to help stabilise any secondary structures formed. The positioning of the side chains on the nitrogen of the amide (as opposed to the alpha‐carbon) also renders the backbones of peptoid sequences achiral and the tertiary amides are more easily isomerised between cis and trans conformations than the secondary amides of a peptide (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The intramolecular O…CO distance should be less than 3.2 Å and the corresponding bond angle 100°–120°. More recently, Raines and coworkers extended this investigation to endothioxopeptides (through the detailed NMR determination of their trans / cis ratios) and others to endothioxopeptoids. In the former compounds, theoretical analyses demonstrated that the energy of the n → π * interaction is higher when the donor atom is sulfur (as compared to oxygen).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in endothioxopeptide a computational investigation revealed that a different type of n → π * interaction, where in this case π * refers to orbitals of an electron poor aromatic ring located in the side chain (linked to the N α ‐atom), does take place, stabilizing the cis ‐rotamer of the donor thionamide group . In these compounds, the n → π * (aromatic) interaction is operative via a new “bridged” mode facilitated by the NαCH orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…To design effective drugs or protein mimetic materials from peptoids, it is essential to understand and control their conformation. Thus, researchers have developed a variety of methods to constrain peptoid structure, including macrocyclization, steric congestion, side chain chirality, and electronic interactions . Most of these rely on bulky, hydrophobic groups, which can dominate the molecular properties and restrict water solubility, hindering the development of biological applications.…”
Section: Introductionmentioning
confidence: 99%